Control of postharvest green mould of citrus by haliscosamine isolated from Haliclona viscosa sponge. (25th March 2014) - Amraoui, Belkassem El; wahidi, Majida El; Fassouane, Aziz
Abstract : The aim of this study was to evaluate the antifungal activity of haliscosamine isolated from Haliclona viscosa sea sponge from the Moroccan Atlantic coast against Penicillium digitatum, the causal agent of citrus green mould. The in vitro antifungal activity of haliscosamine, determined using the agar disc‐diffusion method, showed that haliscosamine and DESOGERME SP VEGETAUX ® (reference product) have fungicidal activity with inhibition diameters of 19 and 18 mm, respectively. Haliscosamine and a positive control (DESOGERME SP VEGETAUX ® ) were tested in vivo in comparison with a negative control on orange fruits in normal storage conditions. This test showed that after four weeks of storage, the rate of decay of citrus fruits treated with haliscosamine or DESOGERME does not exceed 14%, whereas in the negative control the decay rate is 77%. The results of in vitro and in vivo tests indicate that haliscosamine and DESOGERME SP VEGETAUX ® have an important antifungal potential against P. digitatum and that haliscosamine (a natural product) may represent an alternative to the use of chemical fungicides.